Real Exchange Rate Misalignment In Algeria (1980 – 2012) - Madouni, Mourad (جامعة الوادي University of Eloued, 2015)
he purpose of this paper is to estimate the Equilibrium real exchange rate (ERER) of the Algerian Dinar, from 1980 to 2012 by applying the Edward’s model (1989) and Elbadawi (1994) and asses the degree of misalignment. We will use a co-integration method in order to see whether there is a long run relationship between the ERER and its fundamentals such as: terms of trade, import tariffs or openness and for the adjustment in the short run the Error Correction Model (ECM) is used. Our findings are an increase in the oil prices or an improvement in terms of trade of one percent is associated with an appreciation of the REER of about 1,56 %. A decline in openness of one percent appreciates of the REER about 0,8%
اختلال سعر الصرف الحقيقي في الجزائر 1980- 2012
مقال- مجلة رؤى اقتصادية
Keywords: Equilibrium real exchange rate, misalignment, Algerian Dinar; سعر الصرف الحقيقي التوازني، الاختلال، الدينار الجزائري